2002
DOI: 10.1046/j.1460-9568.2002.01981.x
|View full text |Cite
|
Sign up to set email alerts
|

PACAP protects cerebellar granule neurons against oxidative stress‐induced apoptosis

Abstract: Oxidative stress, resulting from accumulation of reactive oxygen species, plays a critical role in neuronal cell death associated with neurodegenerative diseases and stroke. In the present study, we have investigated the potential neuroprotective effect of pituitary adenylate cyclase-activating polypeptide (PACAP) on oxidative stress-induced apoptosis. Incubation of cerebellar granule cells with PACAP inhibited hydrogen peroxide-evoked cell death in a concentration-dependent manner. The effect of PACAP on gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 50 publications
6
133
0
Order By: Relevance
“…It is also of interest that GLP-1 appears to exert a cytoprotective action not only in β-cells, but also in neurons [130]. Such findings extend on previous studies demonstrating that PACAP, a neuropeptide related in structure to GLP-1, exerts a neuroprotective effect within the brain [131]. On the basis of these observations, it may be speculated that one unexpected and beneficial therapeutic action of GLP-1 may be its ability to protect against β-cell apoptosis associated with autoimmune destruction (type 1 diabetes) or β-cell exhaustion (type 2 diabetes).…”
Section: G Newly Recognized Growth Factor-like Effects Of Glp-1supporting
confidence: 74%
“…It is also of interest that GLP-1 appears to exert a cytoprotective action not only in β-cells, but also in neurons [130]. Such findings extend on previous studies demonstrating that PACAP, a neuropeptide related in structure to GLP-1, exerts a neuroprotective effect within the brain [131]. On the basis of these observations, it may be speculated that one unexpected and beneficial therapeutic action of GLP-1 may be its ability to protect against β-cell apoptosis associated with autoimmune destruction (type 1 diabetes) or β-cell exhaustion (type 2 diabetes).…”
Section: G Newly Recognized Growth Factor-like Effects Of Glp-1supporting
confidence: 74%
“…PACAP and BMP-2 are known survival factors for ventral mesencephalic DA neurons that can protect from 6-hydroxydopamine and MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) (32)(33)(34). ANP can counteract oxidative stress and excess NO (35,36), whereas PARM-1 is implicated in suppression of apoptosis (37). The BMP-inducible antagonists follistatin and chordin were also selectively expressed in the VTA, which indicates active BMP-signaling controlled by autoregulatory feedback loops.…”
Section: Resultsmentioning
confidence: 99%
“…Various in vitro studies involving exposure to ␤-amyloid (14), ceramide (15,16), hydroxyl peroxide (17), and ethanol (18,19) have indicated that the neurotrophic PACAP signaling pathway is increased or activated by means of phosphorylation of the extracellular signal-regulated kinase (ERK) type of mitogenactivated protein kinase (15)(16)(17), phosphatidylinositol 3Ј-OH kinase (18), and protein kinase A (18,20) but is decreased or inhibited by means of the phosphorylation of cJun N-terminal kinase (JNK) (15) and the caspases cascade (14,17). PACAP suppresses cell death indirectly by the induction of BDNF in neuronal culture by glutamate toxicity (21,22).…”
mentioning
confidence: 99%